Aplikasi Jemput dan Donor Darah Dengan Teknologi Open Street Maps dan JWT Token Berbasis Android - Nova Putri Octaviani; Rika Idmayanti; Cipto Prabowo (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2022)
The development of information technology rapidly nowadays and lead to mobile development. In this thesis, will be built an android base application which is useful for health because it helps people who have difficulty getting donors and registers to carry out blood donor activities, so people don’t need to look for donors by posting broadcasts on social media because the application will help the process of finding donors to donate blood. This application uses Open Street Maps to get the address of the donor so the recipient can pick up blood and take it to PMI. This application also uses JWT Token to save the login session of each user who enters the application. This application use the internet connection to communicate with AWS server which already installed with Mysql and Apache inside of it. This application is built by Java programming language and use database Mysql. For interaction between android and server that is built an API based on the PHP programming language with PDO method. The result of this thesis will show question and result obtained by student at the time when finish doing the exam on the application